Rejang Pedawa dance as a medium for ethnopedagogical-based adolescent learning - Ardiyani, Luh Putu Cita; Pitriani, Komang; Jero, Ni Wayan Jemiwi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The ethno-pedagogical-based educational approach serves as a medium for the socialization of cultural values, as it contains local content that assists individuals in their social lives. Ethnopedagogical education becomes a variant of the learning process that is conducted by studying local arts in each region. One of these local arts is the Rejang Dance of Pedawa Village. This dance contains cultural values that can provide behavioral orientation to the people of Pedawa Village, especially young women. This research aims to analyze the existence of the Rejang Dance of Pedawa Village as an ethno-pedagogical basis that can be optimized in developing the character of young women. Methods: Research on the Rejang Dance of Pedawa Village as a medium for developing adolescent character based on ethno-pedagogy using a qualitative approach. The data analysis techniques from this research consist of data collection, data reduction, data presentation, and conclusions. This research uses a data collection process consisting of interviews, observations, and document studies. Findings: Dance is considered to develop social, emotional, and cognitive intelligence. Learning dance can serve as a medium for improving social intelligence because its teaching emphasizes interaction within learning groups. The desire to continue learning will also shape the character of